Sound insulation of a hollow concrete blocks wall made with construction and demolition waste and wood-based panels as linings. Issue 4 (December 2021) - Scoczynski Ribeiro, Rodrigo; Pereira de Sousa, Raylton; Santos Deniz Amarilla, Rosemara; Sant'Ana, Luis Henrique; Avelar, Márcio; Catai, Rodrigo Eduardo; Matoski, Adalberto
It is a well-discussed topic that Construction and Demolition Waste (CDW) can be recycled and used as aggregate in the construction sector. Generally, Brazilian construction techniques are based on hollow blocks or bricks and mortars as coating systems. This paper describes the sound insulation of a masonry wall built with hollow concrete blocks and CDW as aggregates. The measurements were performed according to the reverberant chamber method. Keeping sustainability in mind instead of applying cement mortar as coating system, Oriented Strand Boards (OSB) and Wood-Wool Cement Boards (WWCB) were used and also tested as acoustical linings. The panels were directly attached on the wall with nails in the receiving room. All types of panels increased the weighted sound reduction index (R W ). Wood-based composites can also improve the air quality because of their hygroscopic properties. In summary, sustainable wall systems were characterized according to their sound insulation properties, presented as possible substitutes for traditional masonry walls.